2018
DOI: 10.1088/1741-2552/aaac92
|View full text |Cite
|
Sign up to set email alerts
|

A generic EEG artifact removal algorithm based on the multi-channel Wiener filter

Abstract: Current EEG artifact removal techniques often have limited applicability due to their specificity to one kind of artifact, their complexity, or simply because they are too 'blind'. This paper demonstrates a fast, robust and generic algorithm for removal of EEG artifacts of various types, i.e. those that were annotated as unwanted by the user.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
200
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
2

Relationship

3
5

Authors

Journals

citations
Cited by 233 publications
(203 citation statements)
references
References 27 publications
3
200
0
Order By: Relevance
“…In Das et al (2016), it has been shown that this data resulted in significantly better attention decoding performance in comparison to dichotically presented unfiltered stimuli. The multi-channel Wiener filtering (MWF) method in Somers et al (2018) was used on the EEG data for artifact removal. The EEG data was bandpass filtered between 1 and 9 Hz.…”
Section: Validation Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…In Das et al (2016), it has been shown that this data resulted in significantly better attention decoding performance in comparison to dichotically presented unfiltered stimuli. The multi-channel Wiener filtering (MWF) method in Somers et al (2018) was used on the EEG data for artifact removal. The EEG data was bandpass filtered between 1 and 9 Hz.…”
Section: Validation Experimentsmentioning
confidence: 99%
“…Preprocessing of the EEG data was done similar to Vanthornhout et al (2018). The EEG was highpass filtered (second order Butterworth with cut-off at 0.5 Hz) and downsampled to 256 Hz before applying the MWF for artifact rejection (Somers et al, 2018). It was then re-referenced to the Cz electrode (therefore C = 63).…”
Section: Validation Experimentsmentioning
confidence: 99%
“…The EEG data was downsampled from 8192 Hz to 256 Hz similarly to the envelope. Next, a generic EEG artifact removal algorithm (Somers et al, 2018) was applied on the EEG-data to remove eye artifacts similar to described in Decruy et al (2019). EEG-signals were then re-referenced to Cz and bandpass filtered for delta-and theta-band using the same Chebyshev filter as used for the envelope.…”
Section: Signal Processing: Envelope Reconstructionmentioning
confidence: 99%
“…The EEG was first downsampled from 8192 Hz to 512 Hz, similar to Bernarding et al (2014). Then artifacts were removed using a generic EEG artifact removal algorithm (Somers et al, 2018). Consequently, EEG signals were re-referenced to Cz and bandpass filtered using the same Chebyshev filter as used for envelope reconstruction.…”
Section: Signal Processing: Phase Synchronization and Alpha Powermentioning
confidence: 99%
“…Electroencephalography (EEG), for example, is a portable neuroimaging system that can be used to assess different functional brain states [6][7][8][9]. However, a recorded EEG signal is highly contaminated with nonneuronal activities from different sources including eye blinking, eye movements, muscle movements, and electrocardiography (ECG) [10][11][12][13][14][15]. Eye movements and blinking generate high-magnitude artifacts as compared with the pure neuronal activity present in EEG data [16][17][18].…”
Section: Introductionmentioning
confidence: 99%